The Influence of Pioneer Neurons on a Growing Motor Nerve in Drosophila Requires the Neural Cell Adhesion Molecule Homolog FasciclinII - Sánchez-Soriano, Natalia (J Neurosci, 2005)
The phenomenon of pioneer neurons has been known for almost a century, but so far we have little insights into mechanisms and molecules involved. Here, we study the formation of the Drosophila intersegmental motor nerve (ISN). We show that aCC/RP2 and U motor neurons grow together at the leading front of the ISN. Nevertheless, aCC/RP2 neurons are the pioneers, and U neurons are the followers, because only aCC/RP2 neurons effectively influence growth of the ISN. We also show that this influence depends on the neural cell adhesion molecule homolog FasciclinII. First, ablation of aCC/RP2 has a stronger impact on ISN growth than U ablation. Second, strong growth-influencing capabilities of aCC/RP2 are revealed with a stalling approach we used: when aCC/RP2 motor axons are stalled specifically, the entire ISN (including the U neurons) coarrests, demonstrating that aCC/RP2 neurons influence the behavior of U growth cones. In contrast, stalled U neurons do not have the same influence on other ISN motor neurons. The influence on ISN growth requires FasciclinII: targeted expression of FasciclinII in U neurons increases their influence on the ISN, whereas a FasciclinII loss-of-function background reduces ISN coarrest with stalled aCC/RP2 axons. The qualitative differences of both neuron groups are confirmed through our findings that aCC/RP2 growth cones are wider and more complex than those of U neurons. However, U growth cones adopt aCC/RP2-like wider shapes in a FasciclinII loss-of-function background. Therefore, FasciclinII is to a degree required and sufficient for pioneer-follower interactions, but its mode of action cannot be explained merely through an equally bidirectional adhesive interaction.